2022
DOI: 10.19159/tutad.1004550
|View full text |Cite
|
Sign up to set email alerts
|

Rhizoctonia solani and Its Biological Control

Abstract: Rhizoctonia solani is a soil- and seed-borne fungus belonging to class basidiomycete and capable of living free and as a saprophyte in the soil. It is divided into 14 anastomosis groups (AGs), which are incompatible with each other in terms of reproduction and proliferation. It has the potential to cause disease in various annual and perennial fruits, vegetables, and industrial and cereal crops. Plant diseases are mostly controlled by cultural methods; however, sometimes chemical control is also employed for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 106 publications
1
2
0
1
Order By: Relevance
“…Virulence degrees in disease symptoms, host range, and geographical position are crucial features of R. solani isolates, which indicate that there are several strains of the pathogen and provide basic information for disease control [49]. The results presented in this study are consistent with the results of previous studies in the same field, which have shown that R. solani is one of the most widespread and ubiquitous seed-borne fungi in the world, as well as in Egypt [50][51][52][53]. These results are also consistent with previous studies, which have confirmed that there is a major change in the distribution and prevalence of R. solani in different proportions in the seeds of beans [51,54].…”
Section: Discussionsupporting
confidence: 90%
“…Virulence degrees in disease symptoms, host range, and geographical position are crucial features of R. solani isolates, which indicate that there are several strains of the pathogen and provide basic information for disease control [49]. The results presented in this study are consistent with the results of previous studies in the same field, which have shown that R. solani is one of the most widespread and ubiquitous seed-borne fungi in the world, as well as in Egypt [50][51][52][53]. These results are also consistent with previous studies, which have confirmed that there is a major change in the distribution and prevalence of R. solani in different proportions in the seeds of beans [51,54].…”
Section: Discussionsupporting
confidence: 90%
“…produce xanthobaccin, kanosamine, oligomycin A and zwittermicin, which have been recognized as antibiotics having antifungal, antiviral, phytotoxic, cytotoxic, antitumor, and antioxidant properties. It has been shown that the antibiotic 'pyrrolnitrin', produced by the P. fluorescens BL915 strain, defends cotton plants against Rhizoctonia solani in Cd-contaminated soil [250]. There have been several studies into efflux processes.…”
Section: Indirect Mechanisms 621 Production Of Antibioticsmentioning
confidence: 99%
“…A variety of strategies have been used to manage this disease including chemical, physical, crop rotation, resistant cultivars, and biological control [ 9 , 10 , 11 ]. Among these alternative techniques, biological control is the most favorable, owing to its safety, eco-friendliness, and efficiency [ 12 ]. The biological control of R. solani on various crops has been extensively studied [ 10 , 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%